Veno-Venous Extracorporeal Membrane Oxygenation for Acute Respiratory Distress Syndrome During Hemorrhagic Shock. Issue 8 (August 2021) - Raff, Lauren A.; Maine, Rebecca G.; Reid, Trista S.
Abstract : Despite overall improvements in critical care, mortality from acute respiratory distress syndrome (ARDS) remains high. Veno-venous extracorporeal membrane oxygenation (V-V ECMO) is used to rescue patients with severe ARDS. Although V-V ECMO can be life-saving, there are significant risks associated with this therapy. Hemorrhage is one of the most common complications. Therefore, some providers are reluctant to use V-V ECMO in patients with severe ARDS who concurrently have a high risk of bleeding or recent active hemorrhage. Several studies have been published detailing the safety of heparin-sparing or completely heparin-free anticoagulation strategies in patients on V-V ECMO. We present the cases of two patients with hemorrhagic shock and ongoing transfusion requirements who developed severe and refractory ARDS while in the operating room for hemorrhage control. After the massive bleeding was stopped, both patients were placed on V-V ECMO and were managed with minimal or no therapeutic anticoagulation for the duration of their course on V-V ECMO. Both patients required multiple operations and procedures while on V-V ECMO and there were no significant hemorrhagic complications. In conclusion, V-V ECMO can be considered for use in select patients with severe ARDS and high risk of hemorrhage, active hemorrhage, or ongoing transfusion requirements.